The Effects of T-2 Toxin on Preimplantion Embryos and Fetuses of Swiss Webster Mice - AGUS HARYONO (HAYATI Journal of Biosciences, 2007)
T-2 toxin is a toxic and teratogenic mycotoxin produced by Fusarium tricintum which may contaminate cereal, seed, and food. The aim of this research is to find out the effects of T-2 Toxin on preimplantion embryos and fetuses of Swiss Webster mice. Pregnant female of Swiss Webster mice on 0 or 2 day of gestation was injected intraperitoneally with T-2 toxin at doses 0.05 or 0.10 mg/kg body weight (bw) and the dam was observed at 3.5 and 18 days of gestation. At 0 day of gestation, embryos were arrested at one to eight cell and uncompacted morulae stages (P < 0.01) compared to control, in both 0.05 and 0.10 mg/kg bw doses. The cell numbers of late blastocyst at all treated groups were decreased significantly compared to control. At 2 day of gestation, most of embryos were arrested on compacted morulae stage at dose 0.10 mg/kg bw (P < 0.01), the late blastocyst and its cell number were dose-dependently decreased. The live fetuses decreased significantly at all dose of T-2 toxin. No external malformation occurred in the fetuses. Results showed that T-2 toxin given at preimplantation stages inhibited development of preimplantation embryos as indicated by decreased number of live fetuses. Therefore, it was grouped as embryotoxic agent but those dosages did not cause malformation of the external appearance of Swiss Webster mice fetuses. Key words: Fusarium tricintum, T-2 toxin, mycotoxin, preimplantation embryos, embryotoxic